An investigation into the determination of some volatile elements in silicate rocks employing d.c. arc emission spectroscopy in artificial atmospheres - Baumgartner, Friedrich Carl (Department of Geological Sciences, 2016)
The determination of 14 trace elements, namely As, Ag, Bi, Cd, Cu, Ga, Ge, Hg, In, Pb, Sb, Sn, Tl and Zn, in silicate rocks using d.c. arc optical emission spectrography (O.E.S.) and X-ray fluorescence spectroscopy (X.R,F.) was investigated. X.R.F, was shown to be capable of determining Cu, Ga, Pb and Zn in normal silicate rocks and Sn, As and Ge in samples enriched in these latter three elements. Improvement of the sensitivity of the trace elements selected employing d.c. arc excitation in artificial atmospheres was examined in detail. A Margoshes and Scribner (M & S) design gas jet was constructed, and proved to have numerous advantages over those gas jets which incorporate a glass canopy. Excitation in argon, argon-oxygen and nitrogen resulted in many advantages. The most prominent were, remarkable enhancement of the element Zn, and selective distillation of the volatile elements when the d.c. arc was surrounded by argon. The drastic reduction 1.n electrode temperature associated with excitation in argon resulted in an unacceptable decrease in the volatilization rates of the more abundant volatile elements. Several successful methods of overcoming these reduced volatilization rates were found. Increased amperage coupled with a special electrode design was one while the use of a small carrier electrode was another. It was also found that the carrier design electrode was most suitable for use with argon and nitrogen atmospheres as its use promoted selective distillation of the volatile elements. The lack of improvement in volatilization characteristics through the use of additives was attributed to the dominating influence of argon on electrode temperature. The principal advantage of excitation in argonoxygen was the suppression of CN emission essential for ultimate sensitivity of the element Tl. While excitation in nitrogen improved the volatilization characteristics of the more abundant elements, severe CN emission and increased spectral background limited the use of nitrogen to those elements with spectral lines not affected by CN emission.